The performance of five different dried blood spot cards for the analysis of six immunosuppressants. (May 2015) - Koster, Remco A; Botma, Rixt; Greijdanus, Ben; Uges, Donald RA; Kosterink, Jos GW; Touw, Daan J; Alffenaar, Jan-Willem C
Background: The relation between hematocrit, substance concentration, extraction recovery and spot formation of tacrolimus, sirolimus, everolimus, ascomycin, temsirolimus and cyclosporin A was investigated for Whatman 31 ET CHR, Whatman FTA DMPK-C, Whatman 903, Perkin Elmer 226 and Agilent Bond Elut DMS DBS cards.Results & Discussion: We found that all DBS cards showed the same hematocrit and concentration-dependent recovery patterns for sirolimus, everolimus and temsirolimus. At high concentrations, the total hematocrit effects were much more pronounced than at low concentrations for tacrolimus, sirolimus, everolimus, ascomycin and temsirolimus.Conclusion: The tested card types showed differences in performance, especially at extreme concentrations and hematocrit values. It may be useful to investigate the performance of different types of DBS cards prior to analytical method validation.